2012
DOI: 10.5365/wpsar.2012.3.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of prohibition order after a large outbreak of gastroenteritis caused by a norovirus among function attendees

Abstract: This outbreak strongly suggests transmission of norovirus, possibly caused by an infected food handler. Regulatory measures such as prohibition orders can be effective in enforcing infection control standards and minimising ongoing public health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Leone et al (36) found similar results in their literature review of the presence of human norovirus on bathroom surfaces. Norovirus-positive samples were found on toilet seats in five studies (9, 15, 19, 34, 64) and on sink faucet handles (15, 22, 23), toilet flush handles (48), and bathroom door handles (22, 34, 48) in fewer studies. These results suggest that areas further away from the toilet are less likely to harbor norovirus contamination; toilet surfaces (especially the underside of the seat) would be closest to vomiting and diarrheal events during which high numbers of norovirus particles could be shed (3).…”
Section: Discussionmentioning
confidence: 99%
“…Leone et al (36) found similar results in their literature review of the presence of human norovirus on bathroom surfaces. Norovirus-positive samples were found on toilet seats in five studies (9, 15, 19, 34, 64) and on sink faucet handles (15, 22, 23), toilet flush handles (48), and bathroom door handles (22, 34, 48) in fewer studies. These results suggest that areas further away from the toilet are less likely to harbor norovirus contamination; toilet surfaces (especially the underside of the seat) would be closest to vomiting and diarrheal events during which high numbers of norovirus particles could be shed (3).…”
Section: Discussionmentioning
confidence: 99%